Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1998
DOI: 10.1115/98-gt-097
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of the Convective Heat Transfer in Annular Channels With Rotating Inner Cylinder

Abstract: In the internal air system of gas turbine engines or generators, a large variety of different types of annular channels with rotating cylinders are found. Even though the geometry is very simple, the flow field in such channels can be completely three-dimensional and also unsteady. From the literature it is well-known, that the basic two-dimensional flow field breaks up into a pattern of counter-rotating vortices, as soon as the critical speed of the inner cylinder is exceeded. The presence of a superimposed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(33 citation statements)
references
References 1 publication
3
30
0
Order By: Relevance
“…However, for axial Reynolds numbers above 1500 the effect is reversed. Similar results have been observed in the experiments by Jakoby et al [4].…”
Section: Flow Phenomena Flow Phenomena -Rotational Flowsupporting
confidence: 92%
See 4 more Smart Citations
“…However, for axial Reynolds numbers above 1500 the effect is reversed. Similar results have been observed in the experiments by Jakoby et al [4].…”
Section: Flow Phenomena Flow Phenomena -Rotational Flowsupporting
confidence: 92%
“…It was found that the critical Taylor number had the form seen in Equation 2.10 for low axial Reynolds numbers and radius ratios close Contrary to this, Yamada [59] determined that there was in fact a transition zone between flow regimes. The existence of a transition area between the two flows was confirmed experimentally by Jakoby et al [4].…”
Section: Flow Phenomena Flow Phenomena -Rotational Flowmentioning
confidence: 69%
See 3 more Smart Citations